Study the impact of the Interlukines and Vit.E in patients with Atopic Eczema in Anbar Governorate - Haneen Abdullah; Wajeeh Mohammed; Abdullah Hasan (مجلة جامعة الانبار للعلوم الصرفة, 2024)
Atopic Eczema commonly known as “atopic dermatitis” (AD), is a form of “inflammatory skin condition that impairs the skin” barrier and its capacity to retain moisture, “it is the most prevalent chronic skin condition” and is inherited. “Although AD can affect people of all ages, it most often” first manifests in “infancy and early childhood”. Both its duration and its onset in maturity are possibilities , “Patients are impacted not just by the social” stigma associated “with having a visible skin condition”, but also by the disease's extreme itching, which “frequently causes skin injuries and serious sleep difficulties”. Additionally, “emollients (agents that calm, moisturize, and soften the skin) and topical drugs must be applied often”, and “doctor visits are required for condition” care, IL-4 has been “shown in mouse models to be both necessary for the genesis” of AD and “capable of inducing all of the disease's histopathological” symptoms , The “overexpression of IL-4 causes IgE production to rise”, skin inflammation to worsen, “bacterial skin infection to be encouraged, and pruritus” to be mediated, Previous “research demonstrated the critical involvement” of IL-13 in the pathogenesis of AD, “particularly with regard to various disease” pathogenesis factors” like disruption of the skin barrier”, thickening of the epidermis, itching, inflammation”, and infection”, Vitamin E acts as an “antioxidant in cell membranes where it stops the spread of free radical” reactions, however research has “also shown that it has pro-oxidant properties”. Most studies have “proven its relationship with the skin”, including atopic dermatitis.